A micro-based approach to evaluate the effect of water supply on health in Uganda - Raymond Frempong; Lucas Kitzmüller; David Stadelman (Center for Research in Economics, Management and the Arts (CREMA), 2019)
This paper investigates the impact of improved water provision on individual health outcomes in rural Uganda. We merge household and individual panel datasets with sub-county level administrative data on water supply projects. Our approach allows us to estimate fixed-effect panel data models which use temporal and spatial variation at the sub-county level as identifying variation. We find evidence of small effects from more installations of improved water supply on its water usage, health outcomes of household members, and water collection times. Increasing the sub-county rate of improved water sources per capita leads to a reduction in the likelihood of individuals suffering from symptoms of illness associated with inadequate water supply. We argue that our micro-based approach provides a more externally-valid and highly cost-effective means of evaluating scalable development projects.
Keywords: O12; I15; I31; 330; Evaluation; development projects; drinking water; sanitation; child mortality